Peningkatan Kualitas Manajemen Keuangan Menggunakan Aplikasi Android Pada Usaha Mikro Kecil dan Menengah Ima Food - Avininda Dewi Nindiasari; Arizona Firdonsyah (Jurnal Pemberdayaan Masyarakat, 2024)
The PKM activity partner is Ima Food, which is located in Purwomartani Village, Kalasan, Sleman, D.I. Yogyakarta. The primary issue that partners deal with is that they continue to mix up personal and business finances. This is motivated by a lack of skills and the media used to record business financial reports. Do not have Financial Reports because financial records are not optimal. To overcome partner problems, the PKM team offers the following solutions: (1) Financial literacy education related to MSME Financial Management; (2) Assistance using the android application â€œAkuntansi UKMâ€ to facilitate recording and preparing financial reports. This PKM implementation method uses Participatory Learning and Action (PLA) theory. Some of the steps taken are planning, implementation, monitoring and evaluation. The result of this activity is that Ima Food has financial reports that comply with established standards. Through financial reporting using the Aplikasi UKM, partners can calculate the cost of goods sold based on their expenses, not based on the market selling price. This will certainly provide added value to business activities, increase business enthusiasm and expand business capital.